Triggering effect of “therapeutic MSC” - Kordium, V.A.; Irodov, D.M.; Chaikovsky, Yu.B. (Вiopolymers and Cell, 2017)
The use of MSCs as a therapeutic agent is proven to be highly successful in many cases. However, the effects obtained are often temporary, and not leading to complete recovery. The reasons of such phenomenon are discussed in the article and the concept of “triggering effects” of MSCs is substantiated. The effect consists of the fact, that signal molecules, secreted by MSCs after administration, on one hand reduce the cell damage severity, supports and heals the cells. And on the other hand, MSCs induce mobilization and activation of the own (resident) stem cells, which replace the damaged cells. The realization of the therapeutic effect depends on the presence or absence of genetically determined disorders.